Preparation and Characterization of Starch Nanoparticles for Controlled Release of Curcumin - Pang, Suh Cem; Chin, Suk Fun; Siti Nur Akmar, Mohd Yazid (Hindawi Publishing Corporation, 2014)
Curcumin was loaded onto starch nanoparticles by using in situ nanoprecipitation method and water-in-oil microemulsion system. Curcumin loaded starch nanoparticles exhibited enhanced solubility in aqueous solution as compared to free curcumin. Effects of formulation parameters such as types of reaction medium, types of surfactant, surfactant concentrations, oil/ethanol ratios, loading time, and initial curcumin concentration were found to affect the particle size and loading efficiency (LF) of the curcumin loaded starch nanoparticles. Under optimum conditions, curcumin loaded starch nanoparticles with mean particles size of 87 nm and maximum loading efficiency of 78% were achieved. Curcumin was observed to release out from starch nanoparticles in a sustained way under physiological pH over a period of 10 days.